Comparison of Item Difficulty Analyses of Exams Used in Teaching Turkish as a Foreign Language with Instructors’ Perceptions of Item Difficulty - Seçil Alaca; Funda Keskin (Sakarya University Journal of Education)
In numerous studies focusing on assessment and evaluation of teaching Turkish as a foreign language, researchers have frequently identified issues related to the standardization and low validity and reliability of exams. Addressing these issues and investigating the underlying causes is paramount. Given the development of assessment tools by Turkish language teaching centers are typically the responsibility of instructors, it is essential to understand their perspectives regarding these tools. This study aimed to evaluate the perceptions of instructors concerning item difficulty in the context of teaching Turkish as a foreign language. Initially, item analyses were conducted on reading tests included in assessment tools designed by a Turkish language teaching center for B1, B2, and C1 proficiency levels. Instructors from various Turkish language teaching centers were asked to evaluate item difficulty through a prepared questionnaire. Data regarding instructors educational backgrounds, experiences, and involvement in exam creation were collected. Various analytical methods were employed to examine and interpret the obtained data. Item analysis results of examined tests were compared with instructors' perceptions of difficulty using fit analysis. Accuracy of instructors' item difficulty estimates was calculated for each instructor using Error Matrix, and success rates determined. To identify the effects of instructors' characteristics on item difficulty estimation, t-test and ANOVA analyses were performed. These analyses results were interpreted alongside item analyses, and recommendations provided to enhance the assessment and evaluation literacy of instructors teaching Turkish as a foreign language.